(untitled) (Bangladesh Veterinarian, 2024)
Prevalence of mastitis and their antimicrobial resistance in Amtali (sub-district) area of Barguna District were studied. Mastitis was diagnosed by examining the udder and milk of 300 dairy cows. The bacteria were cultured and biochemical tests and antimicrobial profiling were done. The overall prevalence of mastitis was 5.0%, and cross-bred and local cows had 6.4% and 3.8%, respectively. The prevalence was higher in animals 7 - 8 years old (5.9%) and in cows of 3rd - 4th parity (8.8%). Cows with peri-parturient diseases and 1st - 2nd lactation had prevalence of 6.8% (P<0.05) and 5.7%, respectively. The prevalence in dry and wet seasons was 33.3% and 66.7% (P<0.10), respectively, and 53.3% of cows were affected with mastitis when the floor was wet and soiled. The prevalence was 73.3% (P<0.05) in unhygienic conditions. The prevalence of E. coli and S. aureus in mastitis milk samples was 73.3% and 66.7%, respectively. E. coli was sensitive to amoxicillin (36.4%), ampicillin (36.4%), tetracycline (54.6%), streptomycin and co-trimoxazole (81.8%), gentamicin & ceftriaxone (90.9%), cefuroxime and cefixime (100%). S. aureus was sensitive to co-trimoxazole (60%), tetracycline (70%), amoxicillin, ampicillin, streptomycin (80%), gentamicin, ceftriaxone (90%), cefuroxime and cefixime (100%). Bang. vet. 2024. Vol. 41, No. 1 – 2, 13 – 22